Productivity factors and dynamics in Latvia - Baranovs, Olegs; Salmins, Janis; Skribane, Irina (University of Latvia, 2021)
Productivity is crucial factor for the growth of Latvia's economy and prosperity. Although Latvia has achieved significant growth since joining the European Union, productivity growth has slowed in recent years. Today, the world is experiencing a strong shock due to Covid19 crisis, the impact of which on productivity has not yet been widely studied. The aim of this study is to analyse the dynamics of productivity in Latvia, structural changes in technological intensity, as well as the analysis of productivity-related factors. The impact of the Covid-19 pandemic on productivity is also analysed based on researchers' assessments and available information. The research is based on statistical data, studies, and policy documents. It aims to integrate the available data from a broad range of international and domestic sources from the perspective of Latvia. To determine the impact of the redistribution of labour resources on the overall productivity dynamics in the Latvian economy, the shift share analysis method was used. The study shows that the low level of productivity in Latvia is largely related to structural factors - the low level of manufacturing and the dominant position of low-tech industries, the small share of knowledge-intensive industries, the business sector is dominated by SME companies, export structure, etc. The research argues that the redistribution of labour resources in Latvia in favour of more productive sectors is insufficient to have a significant impact on the faster growth of the overall productivity level of the economy. To facilitate productivity, it is important to strengthen innovation and investment in R&D, the new technologies, especially digitization, as well as investing in human capital, improving people's skills and competences.
Keywords: productivity; economic policy; structural factors; Research Subject Categories::SOCIAL SCIENCES